Effects of distance and duration on vertical dynamic visual acuity in screening healthy adults and people with vestibular disorders - Peters, Brian T. (2013)
BACKGROUND: Dynamic visual acuity (DVA) testing may be a useful, indirect indicator of vestibulo-ocular reflex function. Previous evidence shows that acuity for 2 m targets differs little between patients and normals using a 75 ms display duration and that healthy subjects do not differ in acuity when standing and walking while viewing a far target but they do differ when viewing a near target. OBJECTIVE: Improve the protocol of a screening tool by testing the hypothesis that healthy control subjects and patients and with unilateral peripheral vestibular weakness differ on DVA when viewing far targets while seated. METHODS: Controls and patients were tested while they were seated in a chair that oscillated vertically at 2 Hz. They viewed a computer screen 4 m away, while stationary and while moving, with viewing times of either 75 ms or 500 ms. RESULTS: The amount of change between static and dynamic conditions did not differ significantly between patients and controls for the 75 ms condition but controls had lower difference scores than patients when using the 500 ms duration. The ROC value was low, 0.68. Compared to historical data using the 75 ms duration at a distance of 2 m, subjects in both diagnostic groups had better visual acuity at the 75 ms/ 4 m distance. CONCLUSIONS: These results suggest that using the longer duration is better for differentiating patients from healthy controls and they support previous evidence showing that near target viewing is more challenging.